Komunikasi Kiai dalam Kepemimpinan Kolektif di Pesantren Annuqayah Guluk-Guluk Sumenep - Matlani; Fathorrahman (Institut Kariman Wirayudha Sumenep, 2023)
The Islamic boarding school that we have known so far is apparently rich in scientific treasures. It not only contains religious knowledge, but also communication management knowledge. The results of the researcher's observations show that kiai when communicating with students are proof that Islamic boarding schools also offer distinctive and unique communication theories and concepts. This needs to be revealed so that it is known to many groups, so that it can then be put into practice in other institutions and society as well. This research was conducted using qualitative methods, while the data collection techniques in this research used observation techniques and conducting direct interviews as well as documentation techniques. Kyai's communication with santri when the Islamic boarding school was still salaf used verbal communication which centered on the ta'lim assembly and bil hal. When Islamic boarding schools implement formal education and are managed collectively, the kiai's communication with the institutions below is in a top down pattern which is instructive and istikharah, while the kiai's communication with the santri still uses verbal and verbal communication.